Prinsip Komunikasi Islam Dalam Al-Qur’an - Kusnadi; Awaluddin; Zahratunnisa Annur (LP2M IAI Muhammadiyah Sinjai, 2021)
The Koran is the source of the teachings of Islam like an ocean full of wonders and uniqueness that will never be swallowed up by the times. The Koran is the main symbol of prophethood and the main divine treatise which was passed down through the mouth of Jibril to be conveyed to mankind in addition to the Prophet's hadith as an explanation for the Koran itself. Whereas for Muslims the Koran is a guide and there is no doubt in it. Therefore, Muslims are ordered to understand the meaning and content of the Koran to be implemented in everyday life which is also a science. If you look at the concept of science conventionally, it is the result of human reason, senses and intuition obtained through the results of a process built on the basis of the scientific method with all its tools. However, if you look at the concept of knowledge in the Koran, it is the result of the derivation of human reason which is built on the understanding of the qouliyah verses (al-Qur'an) which are the word of Allah, the understanding of the kauniyah verses is Allah's creation. and understanding sunnah / hadith which is the explanation of the Koran